Response to the New Bombs - Bowles, Chester (Tufts Archival Research Center, 2006)
Chester Bowles, Ambassador to India and Nepal and former Governor of Connecticut, describes his belief that an adequate response to the threat of the nuclear age will require cooperation from all sectors of humanity, and that the issue of world poverty must be addressed. Audio also contains advertisement for "This I Believe" book.